2022
DOI: 10.1002/mc.23472
|View full text |Cite|
|
Sign up to set email alerts
|

Doublecortin‐like kinase 1 is a therapeutic target in squamous cell carcinoma

Abstract: Doublecortin like kinase 1 (DCLK1) plays a crucial role in several cancers including colon and pancreatic adenocarcinomas. However, its role in squamous cell carcinoma (SCC) remains unknown. To this end, we examined DCLK1 expression in head and neck SCC (HNSCC) and anal SCC (ASCC). We found that DCLK1 is elevated in patient SCC tissue, which correlated with cancer progression and poorer overall survival. Furthermore, DCLK1 expression is significantly elevated in human papilloma virus negative HNSCC, which are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Unfavorable outcomes in HNSCC patients are often associated with locoregional invasion, a less explored aspect of the disease. Our previous work demonstrated that DCLK1 knockdown reduces cell invasion [15]. In invasive solid tumors, ECM degradation occurs through direct cell-to-matrix contact, facilitated by specialized subcellular invasive structures called invadopodia, with finger-like morphology [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfavorable outcomes in HNSCC patients are often associated with locoregional invasion, a less explored aspect of the disease. Our previous work demonstrated that DCLK1 knockdown reduces cell invasion [15]. In invasive solid tumors, ECM degradation occurs through direct cell-to-matrix contact, facilitated by specialized subcellular invasive structures called invadopodia, with finger-like morphology [25].…”
Section: Resultsmentioning
confidence: 99%
“…Doublecortin like kinase 1 (DCLK1), originally characterized as a microtubule-binding protein, has predominantly been associated with cancer stem cell properties, particularly in colorectal cancer [14]. Its relevance in cancer research stems from observations, including recent findings from our research group, which highlight that inhibiting or genetically abrogating DCLK1 reduces cancer cells’ ability to degrade and invade through an ECM substrate [15]. Notably, DCLK1’s history extends beyond cancer studies and finds its origins in neurobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance of these tumors often limits the therapeutic effect of these treatments and causes unnecessary physical morbidity and economic burden to patients. Therefore, it is imperative to find targets and molecular biomarkers of chemoresistance for better treatment of HNSCC patients 7–10 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to find targets and molecular biomarkers of chemoresistance for better treatment of HNSCC patients. [7][8][9][10] At present, traditional Chinese medicine shows great potential in improving body immunity, reducing drug chemical toxicity, promoting tumor cell apoptosis, and enhancing the sensitivity of these tumors to chemotherapeutic drugs. HNSCC is commonly recognized as a qi and blood condensation type in Chinese medicine identification.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the seventh most common cancer worldwide, contributing to 325,000 deaths and 660,000 new cases every year [1]. Despite recent therapeutic advances, the five-year survival remains below 50% [2]. There is an urgent need for development of effective small molecule inhibitors [3].…”
Section: Introductionmentioning
confidence: 99%